2015
DOI: 10.1002/anie.201500110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbon/Sulfur Nanolaminates by Electrochemical Extraction of Titanium from Ti2SC

Abstract: Herein we electrochemically and selectively extract Ti from the MAX phase Ti2SC to form carbon/sulfur (C/S) nanolaminates at room temperature. The products are composed of multi-layers of C/S flakes, with predominantly amorphous and some graphene-like structures. Covalent bonding between C and S is observed in the nanolaminates, which render the latter promising candidates as electrode materials for Li-S batteries. We also show that it is possible to extract Ti from other MAX phases, such as Ti3AlC2, Ti3SnC2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 43 publications
(22 reference statements)
6
75
1
1
Order By: Relevance
“…As shown in Figure 6a,d, XPS measurements are carried out on the SC-BDSA felt at intermediately discharged (0.8 V), fully discharged (0.01 V), intermediately discharged (0.8 V), and fully charged states (3.0 V), respectively. [29,31] As expected, after charging to 0.8 V (Figure 6c), the majority of S 2− is oxidized to long-chain states with higher binding energies. And spin-orbit coupling gives rise to a doublet in the S 2p peak (2p 1/2 -2p 3/2 ).…”
Section: Investigation Of the Reaction Mechanism Of Sc-bdsa During Cysupporting
confidence: 78%
See 1 more Smart Citation
“…As shown in Figure 6a,d, XPS measurements are carried out on the SC-BDSA felt at intermediately discharged (0.8 V), fully discharged (0.01 V), intermediately discharged (0.8 V), and fully charged states (3.0 V), respectively. [29,31] As expected, after charging to 0.8 V (Figure 6c), the majority of S 2− is oxidized to long-chain states with higher binding energies. And spin-orbit coupling gives rise to a doublet in the S 2p peak (2p 1/2 -2p 3/2 ).…”
Section: Investigation Of the Reaction Mechanism Of Sc-bdsa During Cysupporting
confidence: 78%
“…In addition, it was suggested that the polar-polar interaction is a strong chemical interaction between polar sodium polysulfides and polar host materials. [28][29][30][31] In practice, these oxide and sulfide materials are able to bridge sodium polysulfides through both polar-polar Na-S(O) interaction and Lewis acid-base bonding, depending on the exposed facets to some extent. [25][26][27] Instead of relying on polar-polar interactions, the suitably tailored hosts can bind sodium polysulfides through metal-sulfur bonding.…”
mentioning
confidence: 99%
“…[13] Additionally,Gogotsi and co-workers have developed as elective electrochemical extraction method to fabricate new laminated materials, filling the gap in material composition between pure inorganic materials and carbon materials. [14] Compared to systems employing the physical-confinement technique,t he above highlighted MNCS/CNT and MXene systems exhibited remarkable enhancements of both capacity and cycling stability.Ahigh initial capacity of 1438 mAh g À1 was obtained at ac urrent density of 0.84 mA cm À2 for MNCS/CNT composites with 70 %o f sulfur.T he system also demonstrated excellent cycling stability as after 200 cycles as pecific capacity of approximately 1200 mAh g À1 was retained at ac urrent density of 1.68 mA cm À2 .Furthermore,the system exhibits ahigh sulfur loading of 5mgcm À2 . [15] Considering the MXene d-Ti 2 Chosts, their composites with 70 %ofsulfur demonstrated adischarge capacity of 1090 mAh g À1 at current density 0.84 Ag À1 and al ow decay rate of 0.05 %p er cycle over the course of 650 cycles.…”
Section: Angewandte Highlightsmentioning
confidence: 97%
“…[14] MXene family members could be good candidate electrode material for lithium-sulfur batteries. [15] Nazar and co-workers investigated Ti 2 C(OH) x /S cathodes. [15] Nazar and co-workers investigated Ti 2 C(OH) x /S cathodes.…”
mentioning
confidence: 99%
“…Both precursors show a sharp mass loss in the temperature range of 240-300 °C. [15] Figure S6 in the Supporting Information shows the TEM image of etched-Ti 3 C 2 T x sample after hydrofluoric acid treatment. [18] It should be noted that the mass loss rate of the self-assembled precursor at this stage is lower than that of the mechanically mixed precursor.…”
mentioning
confidence: 99%